Innovative technologies of development and management of electric power industry in the conditions of energy transition - Olga V. Radionova; Rashid A. Sitdikov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the global power industry is undergoing transformation and an energy transition towards alternative energy, accompanied by innovations related to decarbonization, decentralization, and digitalization. There is a need for an overview of various approaches and trends (methodological, intelligent, network-centric, organizational, etc.) affecting the efficiency of the energy transition and the further development of the power industry. Aim: to identify trends influencing the management of decentralized, distributed power systems and to confirm the effectiveness of the network-centric management model for electrical systems with a distributed structure. Methods: International experience and comparative analysis of the influence of trends on energy transition processes in distributed power systems using intelligent, including network-centric, methods are used. Results: the list of trends influencing energy transition processes and the implementation of market relations in the electricity sector has been compiled and systematized. It was established that the network-centric method is most effective for managing distributed electricity grids, as in this approach, the structures of information and energy elements coincide, forming a unified energy-information element. Based on the analysis, corresponding proposals have been made for the efficiency of Uzbekistan's energy transition process through the application of the network-centric management method.